Unveiling Feminist Strike: The Case of "Woman, Life, Freedom" in Iran - Shirin Assa (Atlantis)
In the wake of the death of Jina (Mahsa) Amini, a powerful image emerged: women in Iran defiantly casting aside their hijabs and rallying under the slogan of “Woman, Life, Freedom.” This paper explores and reflects upon what I call following Verónica Gago, a feminist strike in Iran that organizes disorderly and cross-sectoral withdrawals of women from structures that exploit and assault them and restores their bargaining power and agency. Through the analytical perspective of intersectionality, this paper inquires into how the political underpinnings of the gendered apparatus in the Islamic regime of Iran have propelled the imagination of a common body among the diverse array of women. Further, it scrutinizes how the #WomanLifeFreedom uprising unveils a feminist strike and what it entails. This paper aims to show how the feminist strike in Iran expands the notion of strike as a tool against the conditions of work and showcases its all-encompassing basis against living conditions and restrictions on freedom.